Communication of the truth to the patient - Pegoraro, Renzo (Medicina e Morale, 1992)
The communication of the truth to the patient involves both the moral theologian and the doctor, on a level of theoretical reflection and practice. Within the prospect of a possibile interdisciplinary dialogue, in this second part the author indicates the outlines for a better comprehension of the relationship between the doctor and the patient, in terms of alliance, based on trust and mutual respect. This context of loyalty makes a relationship of authentic communication possible, by following a gradual path that leads the patient towards the full truth about his condition. The doctor will be able to assume this responsibility by evaluating the meaning of the individual statements and silences, in the differenc circumstances and situations, out of respect for the dignity of the patient and of the medical profession itself.